Building conflict competent teams - Runde, Craig E. 1951- (Jossey-Bass, 2008)
Understanding how to cool down, slow down, and engage the naturally occurring conflicts among team members is critical to the ultimate success of a team.
Includes bibliographical references (pages 217-223) and index. - Print version record
Keywords: Teams in the workplace -- Management; Interpersonal conflict; Conflict management; Institutional Management Teams; Group Processes; Interprofessional Relations; Conflict, Psychological; Équipes de travail; Gestion; Conflit interpersonnel; Gestion des conflits; BUSINESS & ECONOMICS; Workplace Culture; BUSINESS & ECONOMICS; Corporate Governance; BUSINESS & ECONOMICS; Leadership; BUSINESS & ECONOMICS; Organizational Development; Teams in the workplace; Management; Teamwork; Konfliktlösung; Groupes de travail; Pneumatics; Interpersonal relations